EMPIRICAL STUDY OF GENDER CHARACTERISTICS OF SELF-PERCEPTION OF YOUTH STUDENTS (Psychology Travelogs, 2023)
The article presents the results of an empirical research of the gender characteristics of the self-perception of student youth. A description of the methods and methods used in the research is presented («Twenty Statements for Self-Assessment» test (M. Kuhn, T. McPartland); the self-attitude research method; the «Self-Portrait» test; the «Gender-Role Questionnaire» method (S. Bem); «Gender Identity Study» method (L. Schneider) found that gender stereotypes have a significant impact on the formation of self-awareness among young people. Women express a greater tendency to identify themselves with social roles related to caring for others and emotional intelligence, while how men are more likely to associate themselves with professional roles, achievements, as well as with physical characteristics and competition.Regarding the perception of themselves and the world, women show a more realistic perception, while men tend to have an idealized view. It was also found that women are more inclined to understand themselves in the context of relationships with other people and the surrounding world, while men focus on their personal achievements. A high level of gender identity was found in women in general compared to men.The obtained results emphasize that gender stereotypes can limit the opportunities of young people, preventing them from realizing their potential and making a significant contribution to the development of society.Prospects for further research for a deeper understanding of gender stereotypes in modern society, prospects for further research may include analyzing the impact of gender stereotypes on the choice of professions, revealing the role of the media and socio-cultural environment in the formation of gender perceptions, as well as the development of interventions to reduce the impact of harmful stereotypes at the individual and collective levels.
Keywords: gender; self-perception; youth; stereotypes